2012
DOI: 10.1177/147323001204000311
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the Oxidative Stress Marker γ-Glutamyltranspeptidase at Different Stages of Nonalcoholic Fatty Liver Disease

Abstract: Levels of GGT in fatty liver patients may compensate for mild oxidative stress by repressing 8-OHdG levels and preventing progression to NASH; however further oxidative stress leads to increased levels of 8-OHdG and the development of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 28 publications
1
34
0
4
Order By: Relevance
“…26,27 This would further prevent the possibility of incurring irreparable damage and injury to the liver and liver function. 28,29 There has been some suggestion that high doses of proanthocyanidins can actually cause celluar toxicity. 30 However, these studies have so far been limited to showing these toxic effects directly on cultured cells, and evidence for in vivo effects of ingested proanthocyanidins from foods remains to be determined.…”
Section: Figmentioning
confidence: 99%
“…26,27 This would further prevent the possibility of incurring irreparable damage and injury to the liver and liver function. 28,29 There has been some suggestion that high doses of proanthocyanidins can actually cause celluar toxicity. 30 However, these studies have so far been limited to showing these toxic effects directly on cultured cells, and evidence for in vivo effects of ingested proanthocyanidins from foods remains to be determined.…”
Section: Figmentioning
confidence: 99%
“…The normal level of GGT was 11-50U/L at 37°C [15,18]. The GGT level in serum was measured by using the Qualigent GGT kit [19]. .…”
Section: Methodsmentioning
confidence: 99%
“…Dyslipidaemia in the form of hypertriglyceridaemia, is an important cause of fatty liver [19]. The hepatitis-B and hepatitis-C infections, as causes, were found in 16% (8) and 2% (1) of the cases.…”
Section: Causes Of High Ggt Value Cases No(%) N=50mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in many clinical studies, elevated systemic markers of oxidative stress and lipid peroxidation have been found in patients with NAFLD [53][54][55][56][57][58][59] . Recently, in two studies carried out in patients with NAFLD [60,61] , we found increased oxidative stress in vivo, by measuring urinary 8-iso-prostaglandin F2α (8-iso-PGF2α), which derives from the non-enzymatic oxidation of arachidonic acid [62] , and serum levels of soluble NOX2-derived peptide (sNOX2-dp), which is an indicator of NOX2 activation, a NADPH oxidase isoform involved in ROS generation [63,64] .…”
Section: Imtmentioning
confidence: 99%